Acute intermittent porphyria onset: bioinformatic and genetic analysis of porphyrinogenic xenobiotics and drugs transporter system - Pagnotta, Priscila Ayelén (2024)
Acute Intermittent Porphyria (AIP) is a metabolic disease in which the mutation in Porphobilinogen deaminase is not enough for the manifestation of the symptoms. Previous experimental results have shown that alternative variants in genes of ABC drug transporter (ABCB1: rs1045642, rs2032582, rs1128503; ABCG2: rs2231137) and NR1I2 gene (rs12721613), regulator of ABC transcription, could be involved in the onset of AIP. The aim was to investigate further the influence of ABCB1, ABCG2 and NR1I2 on AIP onset in relation to porphyrinogenic drugs employing bioinformatics tools. For this purpose, three SNVs of ABCB1 (rs1045642, rs1128503, rs20325822), two SNVs of ABCG2 (rs2231137, rs2231) and four SNVs of NR1I2 (rs12721613, rs2472677, rs12721607, rs12721608) were evaluated using different databases: gnomAD; UniProt; GenBank; PharmGKB, association between genetic variants, drugs and clinical manifestations; Gene Expression Omnibus, expression arrays; PreADMET and SwissADME, to estimate whether drugs are substrates/inhibitors of different transporters. Allele frequencies varied among different geographic regions and ethnicities, reinforcing the relevance of local control group analysis. For NR1I2 gene, T allele of rs2472677 was associated with a phenotype of toxicity, an altered metabolism and/or a different efficacy for drugs contraindicated in AIP (Isoniazid, Rifampicin and Efavirenz). Considering models to infer liver toxicity, Rifampicin induced down expression of ABCB1 and 8 CYP genes, including CYP3A4, in primary culture of human hepatocytes (GSE139896); Isoniazid caused differential expression of 11 ABC genes (27.3% down expressed) and 18 CYP genes (61.1% down expressed) in a human liver cancer cell line (GSE168473). Analyzing Free Wilson’s equations to find possible drugs to replace those insecure for AIP patients, some derivatives of Thiofeno[3,2]pyrimidine would represent therapeutic alternatives to Efavirenz. These derivatives would have a differential action as substrates/inhibitors of ABCB1 transporter and CYP. Associations between non-wild type variants of ABCB1 and ABCG2, drugs contraindicated in AIP and a phenotype of toxicity or alteration of metabolism were also found: rs1045642, rs1128503 and rs1128503 for ABCB1 (13, 2, and 2 xenobiotics, respectively); and rs2231137 and rs2231142 for ABCG2 (2 and 10 xenobiotics, respectively). In conclusion, it was observed that contraindicated drugs for AIP patients are associated with toxicity and a differential metabolism in the presence of the studied variants. In turn, these drugs alter the gene expression of drug metabolizing and transporting systems. Bioinformatics tools are a valuable complement for experimental findings and for exploring new approaches and would be of relevance in personalized medicine and pharmacogenetics, a topic of upmost relevance in the pathophysiology of Hepatic Porphyrias.